THE URGENCE OF CHARACTERISTICS DEVELOPMENT IN EARLY CHILDREN'S EDUCATION - Imam Tabroni; Sovani Rizky Handayani; Nita Adiyanti (Education : Jurnal Sosial Humaniora dan Pendidikan, 2021)
Keeping up with the times, it is certainly not an easy thing for educators to shape the character of akhlakul karimah in early childhood, but there is a very long process of application. Akhlakul karimah will be formed if applied as early as possible, and assisted by the stimulation provided by parents, family, environment and school. Educational institutions have an important role when learning at school to apply akhlakul karimah to early childhood, either in the form of explanations or practice. Because if the character is formed from an early age, it is unlikely that the child will be carried away by the environmental currents. Therefore there is cooperation between parents and teachers.